Comparison Of Chlorhexidine 2% And Sodium Hypochlorite 5% As Rewetting Agents On Resin- Dentin Micro Tensile Bond Strength - Malihe Karrabi; Abdol rahim Davari; Alireza Danesh Kazemi (Mashhad University of Medical Sciences, 2016)
Resin- dentin interface hydrolysis is one of the greatest problems in restorative dentistry, Because of collagenolytic and proteolytic activity of dentin enzymes. The aim of this study was to compare the effect of CHX 2% and NaOCl 5% as rewetting agent on resin-dentin micro tensile bond strength.Methods: 45 extracted, human caries-free third molar teeth were collected. After exposing of superficial dentin, etching and rinsing of dentin were done. Specimens were divided into 3 equal groups. In group 1, after drying of dentin, CHX 2% was used as rewetting agent for 60 seconds. In group2, NaOCl 5% used as rewetting agent for 120 sec and in group 3 (control), blot dry technique with water was used for substrate. Adhesive system (SingleBond , 3M ESPE , USA) and composite build up (Filtek Z250 ,3M ESPE , USA)) were applied for all groups. After 6 month storage, μTBS measured for hourglass-shaped specimens. Specimens loaded for micro tensile bond strength until fracture occurred. Results: Micro tensile bond strength of group 1 significantly was higher than other groups (52.67±6.862). There was no significant difference between group 2(18.59 ± 6.081) and group 3(28.84± 6.231). (P= 0.094).  Conclusion: CHX acts as matrix metalloproteinases inhibitor and by preventing dentin collagen degradation can preserve the bond strength after 6 months.